2023
DOI: 10.37965/jait.2023.0184
|View full text |Cite
|
Sign up to set email alerts
|

ChatGPT as an Educational Tool: Opportunities, Challenges, and Recommendations for Communication, Business Writing, and Composition Courses

Abstract: This empirical study examines ChatGPT as an educational and learning tool. It investigates the opportunities and chal-lenges that ChatGPT provides to the students and instruc-tors of communication, business writing, and composition courses. It also strives to provide recommendations. After conducting 30 theory-based and application-based ChatGPT tests, it is found that ChatGPT has the potential of replacing search engines as it provides accurate and relia-ble input to students. For opportunities, the study fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(99 citation statements)
references
References 19 publications
2
94
0
3
Order By: Relevance
“…In the months following the release of ChatGPT, scholars in different subfields of education research began reflecting on the opportunities and challenges arising from LLMs' application in education [77][78][79][80][81]. Some recurring ideas in this literature include the impact of LLMs on assessment practices on one side [52,82,83], as well as LLMs' potential to enable interactive and personalised learning assistance for students [84,85], and lesson planning and assessment assistance for teachers [84][85][86][87][88].…”
Section: Implications For Instructionmentioning
confidence: 99%
“…In the months following the release of ChatGPT, scholars in different subfields of education research began reflecting on the opportunities and challenges arising from LLMs' application in education [77][78][79][80][81]. Some recurring ideas in this literature include the impact of LLMs on assessment practices on one side [52,82,83], as well as LLMs' potential to enable interactive and personalised learning assistance for students [84,85], and lesson planning and assessment assistance for teachers [84][85][86][87][88].…”
Section: Implications For Instructionmentioning
confidence: 99%
“…According to AlAfnan et al (2023), ChatGPT has the potential to replace search engines and can transform learning from theory‐based to application‐based ideas and contents. Recent studies indicate that the users are more likely to use Al‐powered tools over search engines in the future for searching information on the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…17 A recent study by the American University of the Middle East assessed the composition of various texts created by ChatGPT and concluded that it was not competent at writing well-structured essays, supporting the idea that the program must be prompted with a highly organized outline in order to produce an organized response. 18 In another study, Kung et al pointed out that the accuracy of the reasoning of ChatGPT will continue to improve through the maturing of language learning models and the fine-tuning of the prompts. 19 Our study provided a prompt to ChatGPT based on the existing organizational structure of a medical textbook, allowing for organized responses, which likely contributed to the high ranking of organization for the ChatGPT.…”
Section: Discussionmentioning
confidence: 99%